Health literacy and cardiovascular disease prevention: a systematic scoping review protocol - Vanessa Vaughan; Mojtaba Lotfaliany; Bonnie Beasant; Georgie Lee; Sarah Hosking (BMJ Open)
Introduction Health literacy is ‘The skills and resources of a person to access, understand and use information to make decisions, and take action on their own health and healthcare’. Literature investigating cardiovascular disease (CVD) prevention and health literacy often exist in silos, only exploring one element of prevention. This protocol aims to establish a scoping method of articles investigating health literacy and CVD preventive practices or knowledge in lay populations.Methods and analysis A scoping review was deemed the most appropriate study design. The topic was conceptualised, with preliminary searching informing subsequent development of search strings. A search of the following databases will be conducted on 31 January 2022: MEDLINE, Global Health, PubMed, Embase, PsycINFO and CINAHL. Studies included will be published in English, of appropriate design, measuring health literacy and some aspect of primary CVD prevention in lay-populations. These criteria will be tested against 25 ‘pilot’ articles from the results, undergoing necessary review before screening commences. A secondary author will screen 10% of abstracts, with a third subject-matter expert reviewing conflicts.Ethics and dissemination This review will be disseminated through peer-reviewed scholarly networks, most likely including journal publication and conference presentation.Article summary CVD is the leading cause of death around the world. This paper proposes an exploration of health literacy’s relationship with CVD prevention as a whole, contrasting with the more segmented reviews currently published.